TAKING TREATMENT MEASURES IN LIVER PATIENTS - Ashuraliyeva G.K. (American Journals, 2022)
Natural medicine is a system of therapy that administrates natural agents and their derivatives to treat human diseases. This medicine has been used to treat many kinds of human diseases for thousands of years. The treatment protocols of natural medicine are integrative in nature, and are required to utilize the most appropriate therapies to address the needs of the individual patient. Because of the relative convenience, safety and efficacy, natural medicine is now increasing worldwide. Naturopathic doctors are licensed in many areas of the world and regulated partly by law in these areas, which is quite different from various other forms of complementary and alternative medicine. Liver diseases, such as hepatitis, liver cirrhosis and liver carcinoma, are serious health problems worldwide. Nearly half of the natural agents used in treatment of liver diseases today are natural products and their derivatives. Although natural medicine is beneficial and safe, physicians should pay close attention to the potential side-effects of the naturopathic agents, which lead to liver injury, interstitial pneumonia and acute respiratory failure. Therefore, when administrating naturopathic protocols to patients for the treatment of liver diseases, we should try our best to prevent and avoid as much as possible the negative impact of these medicines. This article highlights the current practice and recommended improvement of natural medicines in the treatment of liver diseases and gives some specific examples to emphasize the prevention and management of adverse reactions of the natural agents and suggests that natural medicine should be cautiously used to treat liver problems.